Exploring the Process of Women\'s Confrontation with Symptoms of Pelvic Floor Disorders - Zahra Hadizadeh-Talasaz; Talaat Khadivzadeh; Hossein Ebrahimipour; Nayereh Khadem Ghaebi (Hamadan University of Medical Sciences, 2023)
Background and Objective: Pelvic floor disorders (PFDs) are defined as defects in the muscle and ligamentous plates that cause disorders in the anterior, medial, and posterior walls. Symptoms of these disorders can affect various aspects of a woman's life. The results of the studies show that there is a lack of knowledge regarding this process. Therefore, the present study aimed to explain the process of women 's confrontation with the symptoms of PFDs . Materials and Methods: This qualitative study was conducted between 2017 and 2020. A total of 38 participants were included using a purposive and theoretical sampling method. To answer the research question, data were collected using semi-structured in-depth interviews. To find out how women coped with the symptoms of PFDs, Corbin and Strauss' (2015) grounded theory was used. The data were analyzed in four phases, namely 1- analysis of data for concepts, 2- analysis for context, 3- analysis for process, and 4- integration of categories. MAXQDA10 software was used to manage and analyze the qualitative data. Results: In the present study, the main concern of the participants was "deprivation of normal life" and the theory extracted from the data was "symptom management to normalize the situation". This theory was the result of five actions/responses that included mental exploration by observing symptoms and attempting to find reassurance, attempting to hide the illness, trying to resolve marital conflicts, adopting self-management strategies, and actively following up on treatment. Finally, there was a spectrum of consequences ranging from adjustments to the disease to partial recovery. Participants' concerns were related to the "dominance of symptoms in the dimensions of individual and interpersonal life", which included seven sub-concepts. Conclusion: The main finding of this study was the presentation of the theory of "symptom management to normalize the situation", which explained the process in which women faced the symptoms of PFDs. According to this theory, women sought strategies in various contexts in response to their worries and tried to normalize their lives through management.